A Multilevel Study on Trends in Malaysian Secondary School Students’ Science Attitude: Evidence from TIMSS 2011 - Ismail, Mohd Erfy; Samsudin, Mohd Ali; Md. Zain, Ahmad Nurulazam (International Journal of Asian Social Science, 2014)
The aim of this study was to examine the students’ attitudes towards science achievement among eight grade students. The data used in this study were obtained from Malaysian eighth graders who participated in TIMSS 2011. The approach used in this study involves secondary data analysis. Secondary data analysis involves further analysis of an existing dataset with the aim of addressing a research question distinct from that for which the dataset was originally collected and generating novel interpretations and conclusions. A multilevel modeling was used to analyze the data. Multilevel modeling is a generalization of regression methods, and as such can be used for a variety of purposes, including prediction, data reduction, and causal inference from experiments and observational studies. Findings of this study found that certain demographic factors do play a role in determining the students’ interest on science.